Metal- and Acid-Free Methyl Triflate Catalyzed Meyer–Schuster Rearrangement - Yang, Lu; Zeng, Qingle (Synthesis, 2017)
A novel metal- and acid-free preparation of synthetically useful α,β-unsaturated carbonyl compounds from propargyl alcohols has been realized. This Meyer–Schuster rearrangement process is effectively catalyzed by methyl triflate (20 mol%) to prepare a broad scope of conjugated E-enals and E-enones generally in good to excellent yields (up to 90%). This reaction procedure operates under mild conditions (70 °C), in air, with short reaction times (1 h). Moreover, a carbocation intermediate trapped by the solvent 2,2,2-trifluoroethanol was isolated during this transformation.
Keywords: Meyer–Schuster rearrangement; methyl triflate; propargyl alcohols; α,β-unsaturated carbonyl compounds; metal-free; acid-free